Mechanical properties and antimicrobial analysis of antimicrobial starch-based film - Salleh, Eraricar; Muhamad, Ida Idayu (2007)
Antimicrobial (AM) packaging is one of the most promising active packaging systems. Increase demand in food safety, quality, convenience and environmental concerns associated with the handling of plastic waste has emphasized the importance in developing biodegradable and edible films from natural polymers, such as starch. Starch-based film is considered an economical material for antimicrobial packaging. This study aimed at the development of food packaging based on wheat starch incorporated with chitosan and lauric acid as antimicrobial agents. Chitosan has a widely been used in antimicrobial films, to provide edible protective coating, dipping and spraying for the food products due to its antimicrobial properties. Incorporation of chitosan and lauric acid as antimicrobial agent into starch-based film enhance physical and mechanical properties of starch-based film. The starch-based film also having antimicrobial properties that can extend shelf-life of the food packed. The antimicrobial effect of antimicrobial starch-based (AM) film was tested on B. substilis and E. coli. Inhibition of bacterial growth was examined using two methods, i.e. zone of inhibition test on solid media and liquid culture test (optical density measurements). The control (pure wheat starch) and AM film (incorporated with chitosan and lauric acid) were produced by casting method. From the observations, AM films exhibited inhibitory zones. Interestingly, a wide clear zone on solid media was observed for B. substilis growth inhibition whereas inhibition for E. coli was not as effective as B. substilis. From the liquid culture test, the AM films clearly demonstrated a better inhibition against B. substilis than E. coli.